Perubahan Struktur Vegetasi Pada Sistem Perladangan Gilir Balik Masyarakat Dayak Pitap Kalimantan Selatan - Sri Ulfah; Endah Sulistyawati (Environmental Research Center (PPLH) of Udayana University, 2018)
Shifting cultivation is cultivation system performed alternately from one field to another on forest lands. This study aims to assess changes in structure and composition of vegetation and determine the conditions of environmental factors during shifting period. This research use chronosequence approach at sites with different ages i.e. two, four, six and eight years compared to natural forest using structured form squares (20x100 m2) belt transect comprising several terraced plots. Vegetation parameters were measured for all forms, environmental factors measured were microclimates and edafic factors and soil macro-nutrient content. The results showed that 42 species of 23 families founded in all forms. The vegetation distribution from diameter classes (KD) indicated that KD 0-10 cm had the highest number of individual density from all research site and declined sharply with the increase of KD. The potential regeneration of tree species vegetation component of each site showed some different patterns. In aspect of microclimates, the temperature decreases along with sites age. Edafic factor did not show any clear pattern with increase of sites age for C, N and P, while soil K levels were significantly higher in the youngest site age than the older sites.